1991
DOI: 10.1126/science.1827531
|View full text |Cite
|
Sign up to set email alerts
|

HBV X Protein Alters the DNA Binding Specificity of CREB and ATF-2 by Protein-Protein Interactions

Abstract: The hepatitis B virus (HBV) X gene product trans-activates viral and cellular genes. The X protein (pX) does not bind independently to nucleic acids. The data presented here demonstrate that pX entered into a protein-protein complex with the cellular transcriptional factors CREB and ATF-2 and altered their DNA binding specificities. Although CREB and ATF-2 alone did not bind to the HBV enhancer element, a pX-CREB or pX-ATF-2 complex did bind to the HBV enhancer. Thus, the ability of pX to interact with cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
338
1
2

Year Published

1998
1998
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(348 citation statements)
references
References 37 publications
7
338
1
2
Order By: Relevance
“…Since HBV-X act through ets site of p21 promoter, the relations between HBV-X and ets need to be identi®ed. One possibility is the direct interactions of ets transcription factor with HBV-X resulting in the activation of p21 as in the case of Maguire et al (1991). Another possibility is the activations of ets binding to its binding site through the post-transcriptional protein modi®cations through signal transduction pathways (Lee et al, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…Since HBV-X act through ets site of p21 promoter, the relations between HBV-X and ets need to be identi®ed. One possibility is the direct interactions of ets transcription factor with HBV-X resulting in the activation of p21 as in the case of Maguire et al (1991). Another possibility is the activations of ets binding to its binding site through the post-transcriptional protein modi®cations through signal transduction pathways (Lee et al, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that HBx by itself does not bind to dsDNA and that genes stimulated by HBx lack any obvious consensus sequences (Rossner, 1992) suggest that HBx stimulates transcription presumably by interacting with cellular proteins and/or components of signal transduction pathways. Indeed the transactivation function of HBx has been shown to involve both direct interaction with transcriptional factors such as RPB5 of RNA polymerases (Cheong et al, 1995), TATA-binding protein (Quadri et al, 1995) or ATF/ CREB (Maguire et al, 1991;Williams and Andrisani, 1995) and activation of signal transduction pathways such as ras/raf/MAP-kinase (Benn and Schneider, 1994), protein kinase C (PKC) (Kekule et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…HBx does not directly bind to DNA and may stimulate transcription by interacting with transcription factors or with the basal transcription machinery of host RNA polymerase II and III (Cheong et al, 1995;Haviv et al, 1998;Maguire et al, 1991;Qadri et al, 1996;Williams and Andrisani, 1995). Besides its nuclear function as a transcriptional transactivator, several studies indicated that HBx in¯uences cellular signaling pathways in the cytoplasm as well, which is a function consistent with the predominant cytoplasmic localization of HBx in vivo and in most experimental systems (Benn and Schneider, 1994;Natoli et al, 1994).…”
Section: Introductionmentioning
confidence: 99%